1996
DOI: 10.1097/00000542-199608000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Intrathecal Neostigmine and Epidural Clonidine in Human Volunteers

Abstract: These results support enhancement of alpha 2-adrenergic analgesia by intrathecal neostigmine, but do not demonstrate synergy, as observed in animals. Lack of enhancement of side effects suggests this combination may be clinically useful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
40
0
7

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(50 citation statements)
references
References 19 publications
3
40
0
7
Order By: Relevance
“…2 Spinal neostigmine is advantageous over other currently used spinal drugs as it causes no hypotension (excitation of sympathetic outflow), no sedation, no respiratory depression or neurological dysfunction. 2,3 In our study the mean lowest heart rate during spinal anaesthesia in all the three groups were comparable and statistically insignificant. On comparing the haemodynamic parameters, we found that the mean systolic blood pressure before spinal anaesthesia and the lowest mean systolic blood pressure and lowest mean diastolic blood pressure did not differ significantly between the three groups.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…2 Spinal neostigmine is advantageous over other currently used spinal drugs as it causes no hypotension (excitation of sympathetic outflow), no sedation, no respiratory depression or neurological dysfunction. 2,3 In our study the mean lowest heart rate during spinal anaesthesia in all the three groups were comparable and statistically insignificant. On comparing the haemodynamic parameters, we found that the mean systolic blood pressure before spinal anaesthesia and the lowest mean systolic blood pressure and lowest mean diastolic blood pressure did not differ significantly between the three groups.…”
Section: Discussionsupporting
confidence: 49%
“…2 Spinal neostigmine is advantageous over other currently used spinal drugs as it causes no hypotension (excitation of sympathetic outflow), no sedation, no respiratory depression or neurological dysfunction. 2,3 Bupivacaine was the first local anaesthetic that produced adequate pain relief, without a major effect on motor fibres. 4 Neostigmine has been shown to counteract haemodynamic effects of clonidine and bupivacaine.…”
mentioning
confidence: 99%
“…For these reasons, investigations of low-dose combination therapies with different mechanisms of drug action to induce effective analgesic action should be valuable to reduce adverse effects. Combined administrations of clonidine and morphine (33), clonidine and neostigmine (34), as well as morphine and neostigmine (35), into the intrathecal or epidural space have produced effective analgesia with fewer adverse events. The promising results of our present experiments suggest that i.t.…”
Section: Effects Of K + Channels On Bethanechol-induced Antinociceptionmentioning
confidence: 99%
“…[4][5][6] A recent study demonstrated that the oral administration of donepezil, an approved cholinesterase inhibitor for the symptomatic treatment of Alzheimer dementia, produced an antihypersensitivity effect in rats after nerve injury but not in normal animals; this involved a spinal mechanism. 7 Although the detailed mechanism is not fully understood, manipulations that increase acetylcholine (ACh) release in the spinal cord produce analgesia via both muscarinic and nicotinic receptors.…”
mentioning
confidence: 99%